Al-Mas'udi's Contribution in the Development of Classic Islamic Historiography - Rani Lestari; Nurul Hak; M. Nasihudin Ali (UIN Sumatera Utara Medan, 2023)
This article is titled Al-Mas'udi's Contribution in development Classical Islamic Historiography. The focus of the study in this article is to analyze al-Mas'udi's contribution in development historiography during classical Islam in the bibliographic aspects and methods he used. This article uses historical methods that include heuristic stages, verification, interpretation, and historiography. The approach used is a biographical approach. The results in this article show al-Mas'udi's contribution to the development of Islamic historiography in classical times. The contribution can be seen from the bibliographic aspects and the methods he used. Al-Mas'udi used a lot of empirical data as well as the knowledge he gained from scholars. In addition, he also used the samawi books and the books of Greek philosophers in compiling his work. In the historiographical methods section, al-Mas'udi was instrumental in pioneering the use of the dirayah and thematic methods. Al-Mas'udi's work was recognized by subsequent historians, one of whom was Ibn Khaldun. Nonetheless, al-Mas'udi received criticism for his historiographical work, such as the mythological side of his work, al-Mas'udi's tendency towards Shi'a, and the absence of sources in al-Mas'udi's work.